Kidney transplantation of identical HLA siblings with kidneys from the same donor: A case report - Fernandes, Camila Moror; Freire, Janaína Maria Maia; Aguiar, Maria Isis Freire de; Sousa, Francisca Isabelle da Silva e; Moreira, Tyciane Maria Vieira; Fernandes, Neyara Lima; Silva, Hanna Gadelha; Medeiros, Lívia Torres; Pedrosa, Emiliana Holanda; Andrade, Maria Helena Barbosa de; Pereira, Rosiane Araújo; Medeiros, Janaína de Vasconcelos (Brazilian Journal of Transplantation, 2019)
Purpose: To report the case of renal transplantation of identical HLA siblings with kidneys from the same deceased donor and to analyze the post-transplant complications. Method: Descriptive in nature case study and qualitative approach, with two non-twin kidney receptors with same genetic identity, performed at the Walter Cantídio University Hospital in the city of Fortaleza, Ceará, with data collected from medical records. Data analysis and interpretation were performed by confronting theoretical framework of studies and carried out through digital search for studies indexed in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System online (MEDLINE). Results: Receptors share the same genetic identity and comorbidities (diabetes, hypertension and obesity). The siblings also had similar post-transplant complications, such as cytomegalovirus infection and high blood glucose levels, but the recipient with longer ischemia time and longer hemodialysis time remained hospitalized for more days and had more readmissions in the late post-transplant period. Conclusion: This case shows that ischemia time and pre-transplant hemodialysis time are important predictors of the success of kidney transplantation from deceased donor.